POSSIBILITIES OF BLENDED LEARNING TECHNOLOGY IN THE ORGANIZATION OF EDUCATIONAL ACTIVITIES OF PRIMARY SCHOOL STUDENTS - Alekseeva, Tatiana; Sergeeva, Larisa; Panova, Nataliya (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article substantiates the relevance of using the technology of blended learning as one of the means of personalizing the education of primary school students. In modern conditions for the teacher, the formation of the ability to learn independently on the part of primary school children is becoming a leading priority. This problem is especially relevant in conditions of small schools in classes with low occupancy, in which 2-3 study groups are engaged in the same classroom with one teacher. In this regard, it becomes important to solve the problem of organizing the educational space in such a way that the younger student takes a subjective position in the learning process, actively acts in the development of educational material, is able to carry out planning and self-control, and interact in a small group. The “Change of working areas” model contributes to the solution of this problem. The use of this model in classes with low occupancy allows the teacher to realize differentiation, to work individually with the student at each moment of time, use interactive forms of work in the lesson, and organize regular group work. The aim of the study is to determine and experimentally prove the effectiveness of pedagogical conditions of use in the primary low-grade school model "Change of working areas". The tools and methods that ensure the use of this model in the education of primary school children are described. The formative experiment on the implementation of the “Change of working areas” model has shown positive results: learning using the model has a positive effect on the development of meta-subject and personal learning actions.